Endogenous Viral Elements in Shrew Genomes Provide Insights into Pestivirus Ancient History. (5th September 2022) - Li, Yiqiao; Bletsa, Magda; Zisi, Zafeiro; Boonen, Ine; Gryseels, Sophie; Kafetzopoulou, Liana; Webster, Joanne P; Catalano, Stefano; Pybus, Oliver G; Van de Perre, Frederik; Li, Haotian; Li, Yaoyao; et al.
Abstract: As viral genomic imprints in host genomes, endogenous viral elements (EVEs) shed light on the deep evolutionary history of viruses, ancestral host ranges, and ancient viral–host interactions. In addition, they may provide crucial information for calibrating viral evolutionary timescales. In this study, we conducted a comprehensive in silico screening of a large data set of available mammalian genomes for EVEs deriving from members of the viral family Flaviviridae, an important group of viruses including well-known human pathogens, such as Zika, dengue, or hepatitis C viruses. We identified two novel pestivirus-like EVEs in the reference genome of the Indochinese shrew ( Crocidura indochinensis ). Homologs of these novel EVEs were subsequently detected in vivo by molecular detection and sequencing in 27 shrew species, including 26 species representing a wide distribution within the Crocidurinae subfamily and one in the Soricinae subfamily on different continents. Based on this wide distribution, we estimate that the integration event occurred before the last common ancestor of the subfamily, about 10.8 million years ago, attesting to an ancient origin of pestiviruses and Flaviviridae in general. Moreover, we provide the first description of Flaviviridae -derived EVEs in mammals even though the family encompasses numerous mammal-infecting members. This also suggests that shrews were past and perhaps also current natural reservoirs of pestiviruses. Taken together, our results expand the current known Pestivirus host range and provide novel insight into the ancient evolutionary history of pestiviruses and the Flaviviridae family in general.